Severe and moderate acute malnutrition detection in a rural hospital pediatric outpatient clinic and their comparison with the IAP charts: a two-year study - Ambike, Deepali Abhijit; Haribhakta, Sandhya Vishal; Poyekar, Subhash Shankar; Pingley, Aishwarya Santosh; Naidu, Jyotsna Madhu (International Journal of Contemporary Pediatrics, 2017)
Background: Children with moderate acute malnutrition (MAM) have an increased list of mortality, infections and impaired physical and cognitive development compared to well-nourished children. The Objectives of this study were to diagnose Severe Acute Malnutrition (SAM) and Moderate Acute Malnutrition (MAM) using WHO growth charts as a criterion and to compare the WHO classification with the IAP classification in the diagnosis of SAM and MAM. Methods: A two-year duration cross-sectional study conducted in Pediatric outpatient clinic of a rural hospital from January 2013 to December 2014. In case of moderate acute malnutrition (MAM) was diagnosed as weight-for-height >-3 but <-2 Z scores of the median according to WHO growth standards. We defined MAM as mid-upper am circumference (MUAC) of >11.0 cm and <12.5 cm with no bilateral pitting edema and SAM as MUAC less than 11.5 cm. We compared the values with the IAP charts for diagnosis of malnutrition. Our set up is not a nutrition rehabilitation centre, feeding programmes were not implemented. Results: The distribution of prevalence of SAM and MAM differs significantly across three age groups studied (P-value <0.001). However, it did not differ significantly between boys and girls aged between 6 months to 6 years (P-value >0.05). Of 90 SAM cases, 55 cases (61.1%) had Grade 1 IAP grade of malnutrition, 28 cases (31.1%) had Grade 2 IAP grade of malnutrition, 7 cases (7.8%) had Grade 3 IAP grade of malnutrition. None of the SAM cases fell in Grade 4 IAP. The distribution of prevalence of SAM and MAM differs significantly across various IAP grades of malnutrition (P-value <0.001). Conclusions: The IAP charts used for diagnosing malnutrition did not have any comparative value with the WHO charts used for the SAM MAM detection. WHO grading of SAM and MAM is more sensitive than IAP grading in early diagnosis of under nutrition and facilitate early treatment. Not having a targeted nutrition-specific intervention to address MAM in this set up places these children with MAM at excessive risk of adverse outcomes. Further preventive and curative approaches should urgently be considered.